The Effects of Education on Health: An Intergenerational Perspective - Mathias Huebener (Institute of Labor Economics (IZA), 2018)
This paper presents evidence of substantial causal effects of parental education on children's health behaviours and long-term health. We study intergenerational effects of a compulsory schooling increase in Germany after World War II, which was implemented across federal states at different points in time. Maternal schooling reduces children's smoking and overweight in adolescence. The effects persist into children's adulthood, reducing chronic conditions that often result from unhealthy lifestyles. We find no effects of paternal education. Children's peer environment early in life and increased investments in their education are possible effect channels. The intergenerational effects exceed the direct effects on health.
Keywords: I12; I24; I26; 330; parental education; returns to education; smoking; overweight; compulsory schooling; health behaviour